2014
DOI: 10.1074/jbc.m114.589408
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Regulation of the Human Acetyl-CoA Thioesterase 12 and Interactions with the Steroidogenic Acute Regulatory Protein-related Lipid Transfer (START) Domain

Abstract: Background: The regulation of ACOT12 by ADP and ATP is thought to occur through oligomerization. Results: The structures of apo-ACOT12 and ADP-bound ACOT12 reveal new insights into regulation. Conclusion: ACOT12 is a homotrimer and neither ADP nor ATP alter the oligomeric state of the protein.Significance: These findings provide the first structural insights in the regulation of this enzyme family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…Interestingly, only two of a possible four identical CoA binding sites contained CoA. Superposition of CoA into the unbound sites did not reveal any major clashes nor crystallographic packing perturbations, and thus whilst neither a structural or functional basis for this half-of-sites binding is clear, this half-of-sites activity has been noted across a wide range of thioesterase structures published to date (Forwood et al, 2007;Marfori et al, 2011;Swarbrick et al, 2014) and is present in other structures (e.g PDB entries 2qq2 and 4moc; Structural Genomics Consortium, unpublished work; Swarbrick et al, 2014). The presence of two thioesterase domains is also observed in the TE6 family, and is possibly the result of a gene-duplication and fusion event, since both individual domains possessed similar monomer and quaternary arrangements.…”
Section: Tesb Exhibits Specificity For Octanoyl-coamentioning
confidence: 82%
“…Interestingly, only two of a possible four identical CoA binding sites contained CoA. Superposition of CoA into the unbound sites did not reveal any major clashes nor crystallographic packing perturbations, and thus whilst neither a structural or functional basis for this half-of-sites binding is clear, this half-of-sites activity has been noted across a wide range of thioesterase structures published to date (Forwood et al, 2007;Marfori et al, 2011;Swarbrick et al, 2014) and is present in other structures (e.g PDB entries 2qq2 and 4moc; Structural Genomics Consortium, unpublished work; Swarbrick et al, 2014). The presence of two thioesterase domains is also observed in the TE6 family, and is possibly the result of a gene-duplication and fusion event, since both individual domains possessed similar monomer and quaternary arrangements.…”
Section: Tesb Exhibits Specificity For Octanoyl-coamentioning
confidence: 82%
“…This inclusion of a START-domain is an occurrence that is so far limited to mammalian ACOTs and is suggested to provide an additional level of intrinsic lipid-mediated regulation of the thioesterase activity [8, 23, 27, 30]. Interestingly, the single HotDog domain ACOT13 was originally identified as a binding partner of the minimal START domain protein phosphatidylcholine transfer protein (PC-TP; synonym StarD2) [31].…”
Section: Type II Acotsmentioning
confidence: 99%
“…Like ACOT11, ACOT12 is activated by ATP and inhibited by ADP [55]. Although this ATP/ADP-dependent regulation was previously shown to influence oligomerization [56, 57], recent studies suggest that these nucleotides bind to a distinct site, and are not necessary for multimerization [27]. Interestingly, phosphatidic acids decrease the thioesterase activity of ACOT12 putatively by interaction with the START-domain, suggesting regulation that is linked to metabolic conditions within the cell [57].…”
Section: Type II Acotsmentioning
confidence: 99%
“…4A; quaternary structures of SpPaaI, E. coli-PaaI (PDB 2FS2), T. thermophilus-PaaI (PDB code 1J1Y)). Substrate Specificity, Specific Activity, and Active Site Determination-Because the substrate specificity of SpPaaI has yet to be determined, we assessed the activity for a range of thioester-CoA substrates (4,29). We found that whereas SpPaaI-WT displayed a greater activity for phenylacetyl (PA)-CoA than very short and long chain saturated fatty acyl-CoA substrates, the greatest activity was observed for medium-chain fatty acyl-CoA substrates (Fig.…”
Section: Resultsmentioning
confidence: 99%